Film Marketing and Brand Continuity: The Case of “Redirected/Už Lietuvą!” - Dabrovolskas, Audrius (Information & Media, 2024)
The analysis of the most successful cases in the Lithuanian film marketing, which has also been related with the use of social media and integrated marketing communication, should undoubtedly emphasise an example of Redirected: it reveals a consistent need to promote films in an innovative way which attracts the audience’s attention and motivates them to watch a film, especially in smaller film industries. As the Lithuanian film industry belongs to the smaller ones, innovative marketing communication strategy alone cannot suffice to motivate the audience to watch the film. Therefore, the film itself has to be either very significant (e.g., a sequel) or, as in the case of Redirected/Už Lietuvą, has to extend the sequel while at the same time be “something new, but still familiar” to the film spectators.